Stability for bang-bang control problems of partial differential equations. (2nd December 2018) - Qui, Nguyen Thanh; Wachsmuth, Daniel
ABSTRACT: In this paper, we investigate solution stability for control problems of partial differential equations with the cost functional not involving the usual quadratic term for the control. We first establish a sufficient optimality condition for the optimal control problems with bang-bang controls. Then we obtain criteria for solution stability for the optimal control problems of bang-bang controls under linear perturbations. We prove Hölder stability of optimal controls in .